2022
DOI: 10.1002/ece3.9158
|View full text |Cite
|
Sign up to set email alerts
|

Species turnover in ant assemblages is greater horizontally than vertically in the world's tallest tropical forest

Abstract: Abiotic and biotic factors structure species assembly in ecosystems both horizontally and vertically. However, the way community composition changes along comparable horizontal and vertical distances in complex three‐dimensional habitats, and the factors driving these patterns, remains poorly understood. By sampling ant assemblages at comparable vertical and horizontal spatial scales in a tropical rainforest, we tested hypotheses that predicted differences in vertical and horizontal turnover explained by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…There is limited information on how compositional differences of ant assemblages in the vertical space compares with differences in the horizontal space. In fact, to our knowledge, only two studies have addressed this question, but both have evaluated changes in the structure of ant assemblages within only a few hundred meters (Antoniazzi et al, 2021; Xing et al, 2022). In contrast to the findings of these studies, we found that the overall dissimilarity between the ground and the arboreal assemblages at a given site was, on average, greater rather than less than the dissimilarity between assemblages from the same stratum for horizontal distances up to 1500 km.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited information on how compositional differences of ant assemblages in the vertical space compares with differences in the horizontal space. In fact, to our knowledge, only two studies have addressed this question, but both have evaluated changes in the structure of ant assemblages within only a few hundred meters (Antoniazzi et al, 2021; Xing et al, 2022). In contrast to the findings of these studies, we found that the overall dissimilarity between the ground and the arboreal assemblages at a given site was, on average, greater rather than less than the dissimilarity between assemblages from the same stratum for horizontal distances up to 1500 km.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we asked how dissimilarity in species composition within each vertical stratum is affected by the geographical and the climatic distance between sampling sites and how the level of dissimilarity across the horizontal space compares with the dissimilarity across the vertical space. Studies performed at local scales indicate that the distance‐decay of similarity relationship can be different for assemblages from different vertical strata (Antoniazzi et al, 2021; Xing et al, 2022, but see Leponce et al, 2021), and that dissimilarity can be greater horizontally than vertically (Antoniazzi et al, 2021; Xing et al, 2022). However, it is not clear whether these patterns hold at geographical scales.…”
Section: Introductionmentioning
confidence: 99%
“…This pattern may be explained by connectivity in the canopy via lianas and higher territoriality in canopy ants than ground ants (Antoniazzi et al, 2021). At a smaller spatial scale, Xing et al (2022) only detected distance‐decay pattern vertically, but not horizontally for arboreal ant assemblages in tropical rainforest of Borneo. Such pattern can be attributed to distinct microclimate pattern and low horizontal microhabitat connectivity within the three‐dimensional rainforest (Xing et al, 2022).…”
Section: Ecological Patterns In Vertical Dimensions Across Space and ...mentioning
confidence: 98%
“…At a smaller spatial scale, Xing et al (2022) only detected distance‐decay pattern vertically, but not horizontally for arboreal ant assemblages in tropical rainforest of Borneo. Such pattern can be attributed to distinct microclimate pattern and low horizontal microhabitat connectivity within the three‐dimensional rainforest (Xing et al, 2022). Thus, diversity patterns of different taxa reflect the challenges and opportunities provided by the vertical habitat (depending on their ecological requirements and movement/dispersal traits), resulting in a variety of community turnover patterns.…”
Section: Ecological Patterns In Vertical Dimensions Across Space and ...mentioning
confidence: 98%
See 1 more Smart Citation